Negotiating Meaning in Primary CLIL Classroom: A Micro-genetic Analysis of Teacher-Students Interaction - Ima Isnaini Taufiqur Rohmah; Ikariya Sugesti; Muhammad Saibani Wiyanto (IKIP PGRI Bojonegoro, 2026)
This study examined how teachers and students negotiate meaning in a primary CLIL classroom and how teacher scaffolding supports learners’ understanding of both academic content and English language. Using a qualitative micro-genetic design, the research analyzed interactional sequences recorded during fifth-grade science and social studies lessons delivered through English. The findings reveal that meaning negotiation—manifested through clarification requests, confirmation checks, comprehension checks, and recasts—frequently emerges when students struggle with academic terminology. These negotiation episodes facilitate both linguistic development and conceptual understanding. The teacher’s scaffolding, including linguistic simplification, visual support, modeling, tiered questioning, and non-verbal cues, plays a critical role in mediating these processes. Micro-genetic tracking shows that students’ understanding develops gradually across successive turns, demonstrating how scaffolding becomes internalized during interaction. Overall, the study highlights the interdependent roles of negotiation and scaffolding in shaping effective CLIL learning and underscores the importance of teacher interactional competence for supporting young learners in bilingual content classrooms.